Urban and Rural Household Savings in China. (IMF Working Papers; Working Paper, 1988)
Household savings behavior in China during the past 30 years has been studied by using econometric models with the time-varying-parameter technique. The rural sector and the urban sector are investigated separately. In comparison to previous studies on the same subject, the estimated models of the current study are more robust, and the results of the models are much more in line with results of similar studies of other countries.